A STUDY ON THE USE OF YOUTUBE AS A MEDIA TO PROMOTE STUDENTS’ AUTONOMOUS LEARNING - Sari Ismail, Widya; Samtidar, Samtidar; Farahdiba, Syarifah (JTechLP: Journal of Technology in Language Pedagogy, 2022)
This  research  aimed  to  describe  the  students’  perceptions  of  how  YouTube  promotes students’ autonomous learning. The researchers applied qualitative descriptive methods to achieve the research objective. The instrument used in the data collection was an interview guideline. The subjects of this research were students in English Education Study Program in the  2nd,  4th,  and  6th  semesters  2019  to  2021  academic  years  of  Universitas  Negeri Makassar.  The  interview  sample  was  6  students  using  the  purposive  sampling  technique. Based on the results of this study, the researchers found that YouTube can promote students’ autonomous learning. YouTube is considered flexible, authentic, and motivating as a media to  learn.  It  also  enabled  students  to  have  the  freedom  to  control  their  learning  prosses. Nevertheless, students face challenges in using YouTube as a media for independent English learning.